HUBUNGAN KEHAMILAN IBU USIA MUDA DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS BUMI AGUNG KOTA PAGAR ALAM - ruri maiseptya sari; Suhita Tri Oklaini; Dewi Aprilia Ningsi I; Lozalia Lozalia (Universitas Nazhatut Thullab Al- Muafa Sampang, 2022)
The aims of this study was to determine Relationship between Pregnancy of Young Mother with Incidence of Stunting in the Working Area of ​​Puskesmas Bumi Agung, Pagaralam City. This study uses an analytical survey with a case control approach. The population in this study were all pregnant women, Sample in this study were 36 respondents in the case group (stunting) uses a total sampling technique of 18 people, while for the control sample (not stunting) were 18 people uses a systematic random sampling technique with multiples 6. Collecting data using secondary data. The results of this study were obtained: (1) From 36 respondents there were with 18 (50%) respondents experienced stunting and 18 (50%) respondents did not experienced stunting; (2) From 36 respondents who were pregnant at a young age, there were 15 (41.7%) with aged of <20 years, 18 (50%) with aged of 20-35 years, and 3 (8.3%) with aged of >35 years; (3) There is a significant relationship between Pregnancy of Young Mother with Incidence of Stunting in the Working Area of ​​Puskesmas Bumi Agung, Pagaralam City, with a closed relationship category. It is hoped that Puskesmas will maximize the delivery of information by approaching and providing information to prospective brides during pre-marital consultations, preventing anemia in pregnancy and explaining risk factors that can cause stunting in children.